Peran Orang Tua Terhadap Kesehatan Mental Anak Di Era Generasi Z di Kabupaten Wonosobo, Jawa Tengah - Salamah, Salamah; Fauziah, Puji Yanti; Wibawa, Lutfi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The research aims to analyze influencing factors and role of parents in shaping mental health in generation Z era. The method used descriptive research with qualitative approach. Data collection techniques are observation, interviews and literature study. The data analysis technique used in this research is processing observation data, interviews and literature studies into accurate research data.The research sample was eight fourth grade students at Pungangan 1 public primary school, Mojotengah District, Wonosobo Regency, Central Java. The results of research state that there are three factors influence children's mental health, including; 1) parenting style, 2) interaction between children and parents, 3) parents' understanding of children's mental health in generation Z era. Apart from that, role of parents in maintaining mental health is proven through eight actions; 1) respect, 2) listen, 3) build children's trust, 4) create a positive environment, 5) help children solve problems, 6) set realistic goals, 7) avoid sarcastic comments, and 8) provide encouragement. Based on research results, it was concluded that parents choose a parenting style that suits child's characteristics and plays a role in maintaining child's mental health.